Methodological approaches in development of value estimation of costs of freshwater resources of the water basin by the objects of nature use - Serbov, Mykola (Technology audit and production reserves, 2017)
In the present work, the object of research is the cost evaluation of freshwater resources in the implementation of various economic activities within the boundaries of Ukraine's water basins. It is found methodological mechanisms in estimating the costs of a natural resource at various stages of its preparation and use. When solving the problems posed in the work on the basis of the application of analysis and synthesis methods, comparative comparison and logical generalization, an analysis of the costs of the preparation and use of the freshwater resource is carried out. The estimation of expenses for non-productive losses of a natural resource at primary and special preparation is executed. The scheme of cost estimation of expenses at use of water resources by objects of wildlife management is developed. Thanks to the results of the conducted studies, it is possible to more objective and balanced assessment of cost costs for various types of economic use of water resources. The methodological approach presented in the work is a fairly flexible tool with a free choice of elements of analysis depending on the goals and objects of management